Implementasi IoT untuk Otomatisasi Proses Peminjaman Buku Menggunakan NodeMCU dan RFID Terintegrasi REST API - Ulil Albab; Muhamad Bakhar; Dany Sucipto; Qirom Qirom (Jurnal Publikasi Teknik Informatika, 2026)
Library management at SMK Muhammadiyah Adiwerna still faces obstacles in the manual book lending process, making it less efficient and potentially leading to recording errors. This study aims to implement an Internet of Things (IoT)-based system using NodeMCU ESP8266 and RFID RC522 to automate the book identification and lending process integrated with REST API. The research methods include hardware design, firmware development using Arduino IDE, and system integration via the HTTP POST protocol with a backend based on the Yii2 framework. The results show that the system is able to read the UID of RFID cards, send data to the server, and process verification in real-time. Verification results are displayed via an I2C-based LCD as direct feedback to users. The implementation of this system has been proven to increase efficiency and accuracy in the book lending process, as well as reduce dependence on manual input. In addition, the system provides convenience in monitoring borrowing data in a centralized and integrated manner. The use of this technology supports the digitalization of library services in a more modern way. Therefore, the developed system has the potential to be implemented more widely in other educational institutions.